2020
DOI: 10.1371/journal.pone.0242402
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of life satisfaction, coping strategies and defense mechanisms on perceived stress due to COVID-19 emergency: A chained mediation model

Abstract: The coronavirus disease-19 (COVID-19) pandemic represents a worldwide emergency, which may have harmful consequences on people’s mental health. Parallel to research focused on risk factors, it could be useful to investigate the factors that help to cope with such crises at an emotional level. Therefore, this study aimed to strengthen the role of variables that protect from subjective distress during the COVID-19 pandemic, explore the pathways between satisfaction with life and perceived stress, and consider th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
72
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 64 publications
6
72
1
3
Order By: Relevance
“…In other words, psychological health is not only linked to the application of mature defense strategies, but above all to the appropriate use of a variety of defenses based on the circumstances [42]. To confirm this, previous research has shown an inverse association between adaptive levels of defensive functioning and perceived distress, depressive, and post-traumatic symptoms during the COVID-19 pandemic [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, psychological health is not only linked to the application of mature defense strategies, but above all to the appropriate use of a variety of defenses based on the circumstances [42]. To confirm this, previous research has shown an inverse association between adaptive levels of defensive functioning and perceived distress, depressive, and post-traumatic symptoms during the COVID-19 pandemic [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…These groups have also been identified as experiencing poorer mental health during the pandemic, suggesting that coping strategies can influence how effectively we manage the stress of the pandemic. In contrast, Gori et al (2020) found that the use of approach coping (including planning and active coping) was associated with lower levels of COVID-19 stress.…”
mentioning
confidence: 68%
“…In the context of the COVID-19 pandemic, burgeoning studies support that personal meaning serves as a protective factor against psychological distress amid the viral pandemic (Arslan and Yildirim, 2020 ; Gori et al, 2020 ; Yildirim et al, 2020 ). A renewed sense of personal meaning is suggested to help individuals cope with the traumas and grief over the loss of normalcy during these challenging times (de Jong et al, 2020 ; Lin, 2020 ; Schnell and Krampe, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A renewed sense of personal meaning is suggested to help individuals cope with the traumas and grief over the loss of normalcy during these challenging times (de Jong et al, 2020 ; Lin, 2020 ; Schnell and Krampe, 2020 ). Furthermore, personal meaning has demonstrated to promote life satisfaction, healthy behaviors, and adaptive coping during COVID-19 (Gori et al, 2020 ; Lin, 2020 ; Minkkinen et al, 2020 ). In particular, a person's high meaning in life, life satisfaction, and hope can buffer the psychological stress and fear evoked by the virus pandemic and propel individuals toward altruism in a time that the world needs most (Trzebiński et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%